Celebrity Agenda-Setting: How Celebrities’ Social Media Updates Impact Traditional Newspapers’ Entertainment Content - Obiaje , Kris Martins; Sanusi, Bernice Oluwalanu; Oloyede, I.Bayo; Talabi, FelixOlajide (Corpus Intellectual, 2024)
This study builds on the existing literature regarding the agenda-setting theory as it examined the agenda- setting and self-salience role of celebrities through their social media updates as they influence the entertainment content of traditional Nigerian newspapers. The study answered one question: To what extent have celebrities’ social media updates impacted newspapers’ entertainment content? The study employed quantitative content analysis as a research desig, while it used the convenience sampling method to purposively select four Nigerian newspapers where 1,178 news stories were analysed. Findings showed that Nigerian newspapers rely, to a large extent (44.7%), on social media updates for their entertainment news. Moreover, Instagram remained a platform of choice. The paper recommends that since Instagram has become a considerable repertoire of news content, Nigerian newspapers should also pay attention to other interactive networking sites in their news-gathering effort. The paper also suggests an additional adjunct to the agenda-setting theory—Celebrity Agenda.